Assessing The Impact of Climate and Land Use Land Cover Changes On Flood Risks in The Ankobra River Basin Coastal Area in Ghana - Kamanga Tchaka Pulumuka (University of Cape Coast, 2024)
Besides ocean processes, coastal flood risk is underlined by climate and land use land cover (LULC) changes and intrinsic socio-economic characteristics of coastal inhabitants. This study assessed the impacts of temperature, rainfall and LULC changes on flood risks in the Ankobra River Basin Coastal Area (ACA), in the Western Region of Ghana. Trend analysis using Mann-Kendal trend test (ZMK) was used to assess changes in temperature and rainfall between 1986 and 2021. Maximum Likelihood Classification was used to assess LULC change between 1991 and 2022. Socio-economic data were collected through household interviews comprised of 341 households. A Frequency analysis of socio-economic factors was performed in SPSS, followed by variable weighting using Analytical Hierarchy Process (AHP), development of vulnerability indices using the Square Root of Mean of Product formula and hydrological modelling using the Soil and Water Assessment Tool (SWAT) model. The study showed a significant increase in temperature (ZMK = 3.392). Also, the study found that the basin is dominated by dense vegetation (DV), cultivated/sparse vegetation (CV), built-up/bare land (BL) and water (WT). In all, DV decreased by 46 % at the expense of increase in land covered by CV, BL and WT. These changes had corresponding water yield of 335.64 mm in 1991, resulting in inundation area of 14.89 km2, 494.91 mm in 2008 resulting in inundation area of 23.50 km2 and 481.91 mm in 2021resulting in inundation area of 18.31 km2. The vulnerability of the ACA is principally driven by elevation, distance to coastline, condition of houses and income levels.
xvi,135p:,ill
Keywords: Coastal vulnerability Climate change Flood risk Land use land cover Vulnerability index SWAT Model